Rustam nāma : Dāstān-i manẓūm-i Musalmān shudan-i Rustam bih dast-i Imām ʿAlī ('alayhi al-salām) bih inḍimām-i Muʿjiz-nāma-yi Mawlā-yi muttaqiyān - Āydinlū, Sajjād, (Miras Maktoob, ISBN: 9789004365452., 2019)
In his Meccan days Muḥammad's message was rejected by many as a threat to the values and interests of the community. Among his opponents, there was a merchant called Naḍr b. Ḥārith. From his visits to the city of Ḥīra in Mesopotamia, a cultural melting-pot of Iranian, Christian, and pagan Arab beliefs and traditions, he had brought back stories from Iranian folklore, especially about Rustam and Isfandyār, with which he tried to attract the attention of those listening to Muḥammad's speeches, away from the latter's revolutionary message. This explains why the religious elite of the Persianate world rejected Iranian epic folklore as contrary to the message of Shīʿī Islam, Rustam in particular being viewed as incompatibele with the person of Imam ʿAlī. But folklore being difficult to eradicate, Rustam was often depicted as a Muslim convert and enemy-turned-friend of ʿAlī, like in this poem from Safavid times. A miracle story involving ʿAlī accompanies it.